PERAN MEDIA SOSIAL SEBAGAI INSTRUMEN DAKWAH DAN URGENSI PENGEMBANGAN LITERASI DIGITAL DI LINGKUNGAN MADRASAH - Ahmad Khori; Deni Suhendar; Rosalia Ananta (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The growth of data technology has shifted the landscape for disseminating religious values ​​to cyberspace. Social media has now transformed into a new public space where massive contestation of religious thought takes place. Madrasahs, as formal Islamic learning institutions, hold both a strategic position and significant challenges in responding to this phenomenon. This article aims to analyze the strategic position of social media as a modern da'wah instrument and to identify the urgency of developing digital literacy in madrasahs. Using a library research methodology, this article finds that social media offers flexibility, interactivity, and broad reach for the dissemination of Islamic values, a blessing for all the worlds. However, the effectiveness of this digital da'wah is severely threatened by the proliferation of religious hoaxes, radicalism, the commodification of religion, and the erosion of religious authority online. Therefore, the development of comprehensive digital literacy (encompassing skills, culture, ethics, and digital security) for educators and students in madrasahs is urgent to build a moral defense barrier, uphold the ethics of tabayyun (religious self-discipline), and empower madrasahs from consumers to producers of enlightening da'wah content.